Blockade of Exosome Release Suppresses Atrial Fibrillation by Alleviating Atrial Fibrosis in Canines With Prolonged Atrial Pacing - Yao, Yajun; He, Shanqing; Wang, Youcheng; Cao, Zhen; Liu, Dishiwen; Fu, Yuntao; Chen, Huiyu; Wang, Xi; Zhao, Qingyan (Frontiers in Cardiovascular Medicine, 2021)
Background: Clinical studies have shown that exosomes are associated with atrial fibrillation (AF). However, the roles and underlying mechanisms remain unclear. Hence, this study aimed to investigate the function of exosomes in AF development. Methods: Twenty beagles were randomly divided into the sham group (n = 6), the pacing group (n = 7), and the pacing + GW4869 group (n = 7). The pacing and GW4869 groups underwent rapid atrial pacing (450 beats/min) for 7 days. The GW4869 group received intravenous GW4869 injection (an inhibitor of exosome biogenesis/release, 0.3 mg/kg, once a day) during pacing. Electrophysiological measurements, transmission electron microscopy, nanoparticle tracking analysis, western blotting, RT-PCR, Masson's staining, and immunohistochemistry were performed in this study. Results: Rapid atrial pacing increased the release of plasma and atrial exosomes. GW4869 treatment markedly suppressed AF inducibility and reduced the release of exosomes. After 7 days of pacing, the expression of transforming growth factor-β1 (TGF-β1), collagen I/III, and matrix metalloproteinases was enhanced in the atrium, and the levels of microRNA-21-5p (miR-21-5p) were upregulated in both plasma exosomes and the atrium, while the tissue inhibitor of metalloproteinase 3 (TIMP3), a target of miR-21-5p, showed a lower expression in the atrium. The administration of GW4869 abolished these effects. Conclusions: The blockade of exosome release with GW4869 suppressed AF by alleviating atrial fibrosis in a canine model, which was probably related to profibrotic miR-21-5p enriched in exosomes and its downstream TIMP3/TGF-β1 pathway.